A concretização do direito fundamental ao acesso à moradia: (im)possibilidade de efetivação - Gregorius, Eugênia Amábilis (Universidade do Vale do Rio dos Sinos, 2024)
This work addresses the issue of the constitutional right to housing, offering a perspective on how the implementation of fundamental rights, especially the fundamental right to housing, can be implemented by the Courts, as well with the participation of the entire community, the effective beneficiaries of this right. For this analysis, the first chapter explores the historical evolution of the main models of State, from the Liberal State, the Social State and the Democratic State of Law, to its most current development, the Socio-Environmental State of Law. The study then focuses on the means of ensuring the implementation of rights, specifically social rights. The research turns to the architecture of public policies, in a way that allows the realization of fundamental rights, notably access to housing, thus contemplating the realization of the right to housing, established in the Federal Constitution of 1988. Finally, based on cases considered emblematic, the dissertation analyzes the importance of the courts in making the right to housing a reality. In this context, we can see ADPF 828/STF, reported by Justice Luis Roberto Barroso, who in his vote made it compulsory for the country's courts to set up commissions on land conflicts. And lastly, mention is made of the projects carried out by the Rio Grande do Sul Court of Justice, in an innovative and avant-garde way, aimed at guaranteeing these fundamental rights. Thus, based on this argumentative architecture, we seek to answer the questions that problematize this research, guided by the relationship between the right to housing, public policies and the actions of the Judiciary. The research method is deductive, using a bibliographical research technique.
Keywords: Estado de Direito Socioambiental; Direito constitucional à moradia; Meios alternativos de solução de conflitos; Poder judiciário; Tribunal de Justiça do Rio Grande do Sul; Alternative means of conflict resolution; Constitutional right to housing; Judiciary; Court of Justice of Rio Grande do Sul; Socio-environmental rule of law; ACCNPQ::Ciências Sociais Aplicadas::Direito